Chemical characteristics of cascara tea from several varieties of coffee in Aceh Province. Issue 1 (February 2021) - Murlida, E; Noviasari, S; Nilda, C; Rohaya, S; Rahmi, F; Muzaifa, M
Abstract: In coffee processing, coffee husks are usually thrown out, creating a large amount of waste which can potentially pollute the environment. In several countries, coffee husks have been used as a drink and have a high selling value known as cascara tea. The aim of this study is to determine the differences in the chemical characteristics of cascara tea made from three coffee varieties in Aceh Province. This study used a randomized block design with coffee variety as the single factor, either Arabica, Liberica, or Robusta and analyzed by ANOVA. The parameters analyzed were pH value, total dissolved solids, total phenol, and antioxidant activity. The results showed that coffee varieties affected the pH value, total dissolved solids, and total phenol in the brewed cascara. However, coffee varieties do not affect the antioxidant activity of cascara tea. The average pH value of cascara tea obtained was 5.17, total dissolved solids was 0.54 Brix, total phenol was 0.58 mg GAE/ml and antioxidant activity was 70.02%. The highest total phenolic compounds were obtained from Robusta coffee varieties with 0.64 mg GAE/ml. It is necessary to carry out further analysis of the volatile compounds and their correlation with the resulting cascara tea flavor.